ANALISIS JANUARY EFFECT TERHADAP ABNORMAL RETURN DAN TRADING VOLUME ACTIVITY PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2018 - Silvia Anisa; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTIn the world of stock investment, there is a phenomenon of rising stock prices in January, known as the "January Effect". The purpose of this study was to determine the January Effect phenomenon in the LQ-45 index stock companies with an observation period of 2015-2018. This research is based on a problem in the form of an indication of the tendency of stock returns and trading volumes in January which is higher than the other eleven months.The method used in this research is quantitative analysis method. Where this method uses secondary data in the form of published company financial statements, which are then carried out statistical analysis using paired sample t-test. By using efficient market hypothesis theory and anomalous theory.Based on the results of the t-test using significance (α) 0.05 shows that there is no significant difference between the level of stock returns and trading volume before and after January 1. With the three research periods the results of the sig t showed a positive value. It could also be caused in Indonesia has a different tax year.Keywords: January Effect, Abnormal Return, Trading Volume Activity.